Brush back [compact disc, unabridged] - Paretsky, Sara (Paretsky, Sara. V.I. Warshawski novel., 2015)
No one would accuse V. I. Warshawski of backing down from a fight, but there are a few she'd be happy to avoid. High on that list is tangling with Chicago political bosses. Yet that's precisely what she ends up doing when she responds to Frank Guzzo's plea for help.